Pemanfaatan Teknologi Untuk Meningkatkan Keterampilan Anak Dalam Menghadapi Tantangan Generasi Emas - Rahmawati, Elmi; Indra, Novalia; Zurwanty, Recy Harviani (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
Indonesia’s Golden Generation 2045 is a major national aspiration that requires early preparation of human resources, particularly children as the nation’s future successors. In an ever-evolving digital era, technology plays a strategic role in supporting children's development, especially in enhancing essential skills needed to face future challenges. This study explores how the proper use of technology can serve as an effective tool to develop children’s skills such as critical thinking, creativity, communication, and collaboration. By integrating digital media, educational applications, and interactive learning methods, children can engage in learning in a more interesting and relevant way for the demands of the modern age. However, the use of technology must be balanced with wise guidance and supervision from both parents and educators to prevent potential negative impacts. The findings show that when used optimally, technology can be a powerful instrument in shaping resilient, adaptive, and competitive children, well-prepared for the era of the Golden Generation.